ERROR IN PROCESSING PARTS MADE OF HARD-TO-PROCESS ALLOYS AND ITS ANALYSIS - Dubrovets Lyudmila Vladimirovna; Zayniyev Xudoyberdi Muhiddinovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article covers the analysis of components of the cutting errors before choosing the type of control and presents a model of processing error based on analysis of reasons that cause deviation from linear dimensions during machining.